Enhancing Concrete Performance with Fly Ash and Cellulose Nanocrystals: A Comprehensive Study - Varsha, Varsha More; Surekha Bhalchandra; Sanjay Jamkar (International Journal of Sustainable Construction Engineering and Technology, 2025)
The production of concrete is heavily dependent on cement, which plays a major role in environmental challenges like high carbon emissions. This research examines how incorporating fly ash (FA) and cellulose nanocrystals (CNC) affects the characteristics of concrete. FA partially replaced cement at 0-50%, while CNC was added at 0-1% by cement mass. The optimal mix (FA20CNC0.2) with 20% FA and 0.2% CNC showed significant improvements in mechanical properties compared to conventional concrete: 36.54% higher compressive strength, 19.94% higher split tensile strength, 18.22% higher flexural strength, and 21.21% higher shear strength. Regression models with high accuracy (R² > 0.95) were developed to predict secondary mechanical properties from compressive strength, streamlining the mix design process. SEM analysis revealed a denser microstructure with fewer microcracks in FA20CNC0.2. EDS indicated higher amounts of strength-enhancing components like CaCO3 and SiO2. The synergistic effect of FA and CNC improved hydration, pore-filling, and C-S-H bond formation. This approach reduces cement use while enhancing performance, offering an eco-friendly solution for sustainable high-performance concrete production.